Akupunktur dalam Penanganan Nyeri Otot Leher akibat Sindrom Angin-Dingin: Sebuah Studi Kasus Ilustratif - Kurniawan Kurniawan; Puspo Wardoyo; Leny Candra Kurniawan (Universitas Respati Indonesia, 2026)
Neck muscle pain is a common musculoskeletal disorder that may reduce work productivity, particularly among computer users. From the perspective of Traditional Chinese Medicine (TCM), neck muscle pain may be associated with Jing Bi caused by Wind-Cold pathogen invasion, leading to obstruction of Qi and Blood flow in the meridians. This study used a descriptive illustrative case study design involving a 35-year-old male patient with non-traumatic neck muscle pain consistent with Wind-Cold Syndrome. The aim of this study was to describe the patient’s clinical response after receiving acupuncture intervention using a combination of local and distal points. Data were collected through history taking, examination based on the Four Diagnostic Methods of TCM, pain intensity measurement using the Visual Analog Scale (VAS), and evaluation of cervical range of motion (ROM) before, during, and after the intervention. The intervention was conducted in twelve sessions over six weeks at a clinic in Tangerang using GB20, GB21, SI3, TE5, LI4, and Ashi points. Observational findings showed a decrease in VAS score from 8 to 0 and recovery of cervical ROM by the end of therapy. These findings suggest that acupuncture may provide clinical improvement in a case of neck muscle pain associated with Wind-Cold Syndrome. However, as this study was limited to a single case, the findings are illustrative and cannot be generalized without further studies involving larger samples and stronger research designs.